2009
DOI: 10.1111/j.1365-2486.2008.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

On carbon sequestration in desert ecosystems

Abstract: Recent reports of net ecosysytem production >100 gCm À2 yr À1 in deserts are incompatible with existing measurements of net primary production and carbon pools in deserts. The comparisions suggest that gas exchange measurements should be used with caution and better validation if they are expected to indicate the magnitude of carbon sink in these ecosysytems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 24 publications
2
86
0
1
Order By: Relevance
“…This conclusion is strengthened by the results obtained from the diffusion experiments, which showed that, in sterilized calcareous soils, the resulting CO 2 concentrations were lower than expected if diffusion was the only active process. Several previous studies arrived at the same con- clusions by noting the mismatch between the measured and modeled CO 2 fluxes or even by drawing on the results of geochemical modeling (Eshel et al, 2007;Hastings et al, 2005;Schlesinger et al, 2009;Serrano-Ortiz et al, 2010). However, to the best of our knowledge, this study provides the first confirmation and quantification of this effect by O 2 monitoring in intact soil profiles.…”
Section: Relationships Between Co 2 and Soil Respiration In Calcareoumentioning
confidence: 51%
See 1 more Smart Citation
“…This conclusion is strengthened by the results obtained from the diffusion experiments, which showed that, in sterilized calcareous soils, the resulting CO 2 concentrations were lower than expected if diffusion was the only active process. Several previous studies arrived at the same con- clusions by noting the mismatch between the measured and modeled CO 2 fluxes or even by drawing on the results of geochemical modeling (Eshel et al, 2007;Hastings et al, 2005;Schlesinger et al, 2009;Serrano-Ortiz et al, 2010). However, to the best of our knowledge, this study provides the first confirmation and quantification of this effect by O 2 monitoring in intact soil profiles.…”
Section: Relationships Between Co 2 and Soil Respiration In Calcareoumentioning
confidence: 51%
“…Such processes have been shown to influence the temporal variation in the soil CO 2 efflux and to make it different than the biological process of respiration (Benavente et al, 2010;Cuezva et al, 2011;Emmerich, 2003;Eshel et al, 2007;Hastings et al, 2005;Kowalski et al, 2008;Roland et al, 2013;Schlesinger et al, 2009;Serrano-Ortiz et al, 2010;Tamir et al, 2011;Ma et al, 2013;Stevenson and Verburg, 2006;Wang et al, 2014). Third, processes within roots may also cause the CO 2 efflux to be different from the actual respiration rate.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 sink reported here is not in the saline/alkaline soils themselves [Rengasamy, 2006;Schlesinger et al, 2009] but in the groundwater beneath (Figures 1 and 4b). We found that the direct flux of CO 2 into saline/alkaline soils, as proposed by Xie et al [2009], is only a transient flux and thus is not related to the carbon sink [Stone, 2008].…”
Section: Discussionmentioning
confidence: 87%
“…The findings remain controversial, however, because the carbon apparently removed from the atmosphere has not been observed in terrestrial ecosystems [Schlesinger et al, 2009]. The two known active carbon pools on land, living biomass and soil organic carbon, are unlikely to accumulate carbon at such high rates because deserts are sparsely vegetated with humus-poor soil [Schlesinger et al, 2009]. It is also impossible for carbonate accumulation to reach such high rates since it is limited by air deposition of calcium [Schlesinger et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation